Motivasi Aktivitas Bersepeda Yang Dilakukan Mahasiswa Asrama Universitas Negeri Surabaya Pada Sore Hari - Nadia Windasari; Made Pramono; Pudjijuniarto Pudjijuniarto; Fatkur Rohman K (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Becoming a student is a blessing that not everyone can experience, where you start far from your hometown and then have to adjust to new activities, environments and even friends. It is not uncommon to find students who have irregular lifestyle habits, unhealthy eating patterns, often stay up late and rarely exercise. This study aims to determine the type of activity, frequency, duration and level of motivation for cycling sports activities carried out by boarding students at Surabaya State University. The type of research used is descriptive research with a quantitative approach. The population in this study were students living in the Surabaya State University dormitory. The research was conducted in February-March, the data collection technique used was by distributing questionnaires. The research results show that 50% of students more often do light activities such as sweeping, mopping, walking or playing chess, 38% do moderate activities such as jogging, cycling and gymnastics, and 12% of students do heavy activities such as swimming, football and martial arts. Data on the frequency of cycling activities carried out by dormitory students shows that 55% of students do cycling with a frequency of 1-2 times a month, 32% with a frequency of 1-2 times a week, 6% with a frequency of 3-5 times a week, 1% 6 -7 times a week, and 6% have never done cycling in the last month. The majority of students (43%) do cycling for 16-30 minutes. The goals of cycling carried out by students based on health management received the highest index value, namely 82.81 (M=3.37), skills development with a value of 76.56 (M=3.07), social affiliation with a value of 76.16 (M=2.97), image with a value of 70.12 (M =2.87), as well as social recognition with a value of 63.68 (M=2.54).